1977
DOI: 10.1302/0301-620x.59b2.873983
|View full text |Cite
|
Sign up to set email alerts
|

Conformity in condylar replacement knee prosthesis

Abstract: Experiments were carried out to determine the optimum conformity between the femoral and tibial condyles in condylar replacement knee prostheses. Wear tests and observations from removed prostheses indicated that both high and low conformity produced characteristic abrasion and fatigue. Partly conforming condyles provided stability under load-bearing but allowed laxity to occur. Fixation to resist the various forces on the tibial components was enhanced by a short central intramedullary peg. Partial conformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This is due to the differences in contact area and congruity between tibial and femoral components which determine the contact stresses. Previous studies have indicated that contact stresses in the knee often exceed the yield strength of UHMWPE (Walker and Hsieh 1977, Walker 1988.…”
mentioning
confidence: 98%
“…This is due to the differences in contact area and congruity between tibial and femoral components which determine the contact stresses. Previous studies have indicated that contact stresses in the knee often exceed the yield strength of UHMWPE (Walker and Hsieh 1977, Walker 1988.…”
mentioning
confidence: 98%
“…An interposition between the femoral and tibial components appears theoretically to be more attractive than partially constrained prostheses because contact stresses arising from rolling of the femoral condyle on the conforming meniscal components are reduced (Walker and Hsieh, 1977) as the meniscal component is not fixed, but slides on the tibial component, the T-slot in the tibial component just serving as a locator. The number of degrees of freedom is larger than in the constrained prostheses, the greater the constraints the greater the shear forces at the cement/bone junction, leading to an increased likelihood of loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Having proposed that a peg would provide superior fixation to other contemporary methods, an experimental model was constructed to test out the hypothesis. The model consisted of a 6-channel knee simulating machine where cyclic loads and motions were applied to different components affixed to cadaveric tibias and tested over millions of cycles (Walker and Hsieh, 1977). The onepiece pegged components were clearly superior in fixation.…”
Section: Fixation Of Femoral and Tibia Componentsmentioning
confidence: 99%